Fluoride level in plasma blood and urine of first-trimester pregnant women living in a province - Chaiwong, Sanhawat; Chaiwong, Tippawan; Nunthachai, Benjawan; Sripirom, Korparakamon (Health Science, Science and Technology Reviews, 2018)
The study was aimed to determine the fluoride level in blood and urine of 154 first-trimester pregnant women among 7 public hospitals of a province. The concentration of plasma-blood fluoride was not determined in all subjects. For concentration of urine fluoride concentration, 77 cases (50.6%) had low fluoride level (less than 0.2 mg/L), 74 cases (48.7%) revealed the normal fluoride level (0.2 to 3.2 mg/L. Only 3 subjects (1.97) had high fluoride level (more than 3.2 mg/L).